Application of swot analysis in the development and promotion of enriched drinks - Устенко, Інна Андріївна (Eastern-European Journal of Enterprise Technologies, 2015)
Technological factors are one of the four PEST analysis components. The purpose of their research is to identify trends in the technological development, which are the causes of market changes and losses, and emergence of new products. The advantages of new enriched drinks compared to traditional nectars were considered to compile SWOT analysis. Fillers production technology, based on gentle non-thermal physical separation of a water share from apple pomace and pumpkins, and enriched drinks based on them was given. The developed enriched drinks based on fruit and vegetable fillers contain about 10 times more dietary fibers, 30 times more carotene and 11 times more calcium than nectars produced by traditional technologies. The studies were aimed at developing the competition tactics and providing competitive advantages of enriched drinks using SWOT analysis to promote enriched drinks. Thus, market technological factors, namely the strengths and weaknesses of enriched juice drinks based on fruit and vegetable fillers that can facilitate or inhibit the promotion and position consolidation of this product in a certain market segment were analyzed. It was found that by processing apple pomace, apple juice production wastes and pumpkins, prices of juice drinks remain similar to prices of nectars produced by traditional technologies. As primary directions for the effective promotion of enriched drinks in the market of juices and soft drinks, merchandising should be highlighted - without the possibility to use direct advertising to promote a new product it is advisable to stimulate sales through indirect communications, which are less expensive but equally effective.